Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.36570/jduhs.2022.2.1639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interferential Therapy and Elastic Band Exercises on Subjects with Round Shoulder and Forward Head Posture: A Randomized Trial

Abstract: which leads to RSP are characterized as protraction, downward rotation, and anterior tipping of scapula and this may increase upper thoracic kyphosis and cervical lordosis. These factors are the major predisposing 7 factors which leads to upper quadrant pain too. Photographic posture analysis is a basic observational 8 method to detect the FHP with reliability of >0.972. Interferential therapy (IFT) is an established therapy which is used to treat pain. This is also effective for 9 providing relaxation of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…The other possibility is that the sample demographic in this study was asymptomatic. Therefore, such findings of the current study may not be in line with those of previous studies [ 3 , 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…The other possibility is that the sample demographic in this study was asymptomatic. Therefore, such findings of the current study may not be in line with those of previous studies [ 3 , 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Pawaria et al [ 6 , 7 ] reported that a six-week cervical stabilization exercise program was effective in improving FHP, pulmonary function, and respiratory muscle strength in patients with chronic neck pain associated with FHP. Joshi and Sheth [ 3 ] demonstrated that 12 weeks of McKenzie self-treatment could improve FHP and increase peak expiratory flow rate (PEFR) in adolescent girls with FHP. These conflicting findings may be due to the duration of treatment provided in the present trial (a four-week program) not being sufficient to make changes in FVC in subjects with FHP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance bands can be used in combination with posture programs that include strengthening and stretching exercises to correct FHP. Resistance bands can improve functional activity, strength, and balance [ 16 ]. In individuals with UCS, certain muscles, such as the sternocleidomastoid (SCM), scalene, pectoralis minor, and upper trapezius (UT), can become overactive during breathing, leading to reduced activation of the diaphragm, which is the primary dynamic muscle involved in breathing [ 17 ].…”
Section: Introductionmentioning
confidence: 99%